ANALISIS BIAYA VARIABEL SEBAGAI DASAR PENENTUAN HARGA JUAL PRODUK - Kelvin Yudha Napitupulu; Redi Vadli S Saragih; Yoga Bill Rano Manik; Hamonangan Siallagan (Komunitas Manajemen Kompetitif, 2026)
Determining the appropriate selling price is a crucial factor in maintaining a company’s profitability and competitiveness. This study aims to examine the application of the variable costing method as a basis for determining product selling prices and its benefits for managerial decision-making based on a synthesis of various previous studies. The research method used is a literature review by analyzing scientific journal articles relevant to the fields of management accounting and cost management. The results of the literature review indicate that conventional calculations of the cost of goods manufactured (COGM) using the full costing method often lead to rigid pricing decisions in fluctuating market conditions. In contrast, the application of the variable costing method provides contribution margin information that helps management determine selling prices more flexibly, competitively, and accurately for short-term decision-making.